2021
DOI: 10.1101/2021.11.30.470581
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid and efficient adaptation of the dTAG system in mammalian development reveals stage specific requirements of NELF

Abstract: SUMMARYTargeted protein degradation methods offer a unique avenue to assess a protein’s function in a variety of model systems. Recently, these approaches have been applied to mammalian cell culture models, enabling unprecedented temporal control of protein function. However, the efficacy of these systems at the tissue and organismal levels in vivo is not well established. Here, we tested the functionality of the degradation tag (dTAG) degron system in mammalian development. We generated a homozygous knock-in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…(A) Illustration of the NELFB-dTAG system and the corresponding effect on the NELF complex. Following NELFB depletion with dTAG, the NELF complex dissociates and is no longer found bound to chromatin ( 93 ) (B) Heatmaps showing PRO-seq signal in untreated (control) mESCs (left), the fold-change in PRO-seq signal following 30 minutes of dTAG treatment and after 60 minutes of dTAG treatment near TSSs as well as the fold change in PRO-seq signal at 30 minutes and 60 minutes of dTAG treatment compared to untreated control and at 60 minutes compared to 30 minutes of dTAG treatment. (C) A line plot showing the median enhancer-promoter contacts over background ratio change relative to the untreated (T=0) control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(A) Illustration of the NELFB-dTAG system and the corresponding effect on the NELF complex. Following NELFB depletion with dTAG, the NELF complex dissociates and is no longer found bound to chromatin ( 93 ) (B) Heatmaps showing PRO-seq signal in untreated (control) mESCs (left), the fold-change in PRO-seq signal following 30 minutes of dTAG treatment and after 60 minutes of dTAG treatment near TSSs as well as the fold change in PRO-seq signal at 30 minutes and 60 minutes of dTAG treatment compared to untreated control and at 60 minutes compared to 30 minutes of dTAG treatment. (C) A line plot showing the median enhancer-promoter contacts over background ratio change relative to the untreated (T=0) control.…”
Section: Resultsmentioning
confidence: 99%
“…PRO-seq data ( 30, 33 ) for Jurkat T-cells were downloaded from GSE66031 and for K562 from GSE60455. PRO-seq data for mECSs harboring a homozygous endogenous NELFB-FKBP12 F36V fusion protein, treated and untreated with dTAG-13 ( 93 ), were downloaded from GSE196653. GRO-seq data for mESCs ( 47, 86 ) were downloaded from GSE43390 and GSE48895.…”
Section: Data and Code Availabilitymentioning
confidence: 99%
“…Molecularly, profiling of Pol II pausing across pre-implantation mouse development has identified a distinct reduction in Pol II pausing following Zygotic Genome Activation (ZGA) until late blastocyst stage, at which point it is re-established (Liu et al, 2020). We recently showed that NELF is required at this specific stage prior to ZGA to regulate the major ZGA wave in mouse embryos (Abuhashem and Hadjantonakis 2021). At the cellular level, several studies investigating tissue-specific Nelfb knockouts have revealed that functional defects are observed when Nelfb -/- tissues are challenged by an external stimulus, such as an injury or an infection or the need to regenerate in the context of muscle stem cells, the uterine and intestinal walls, and in macrophages (Hewitt et al 2019; Ou et al 2021; Robinson et al 2021; Yu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that a detailed understanding of the dynamic regulation of oocyte and preimplantation proteomes and functions of individual proteins will be facilitated through a combination of genetic modifications to allow tagging of proteins for in situ detection, spatial imaging, and monitoring, and to allow experimentally induced degradation and replenishment of proteins in a controlled manner. Recent technologies allowing for insertion of tags through homology‐mediated DNA editing provide such opportunities (Abuhashem & Hadjantonakis, 2021; Gu, 2020).…”
Section: How Are Maternal Proteins Stored and Regulated?mentioning
confidence: 99%